UPAYA MENINGKATKAN KETERAMPILAN MENYIMAK APRESIATIF CERITA SISWA KELAS V SEKOLAH DASAR PONDOK BAMBU 02 DENGAN MEDIA SINIAR - Jasmine Indria Adiesty; Juhana Sakmal; Petrus Paulus Mbette Suhendro (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to improve students' appreciative listening skills for stories using podcast media in class VB at SDN Pondok Bambu 02 Jakarta, consisting of 31 students. This research is a class action research using the Kemmis and McTaggart model, conducted in two cycles, with each cycle consisting of three meetings. The minimum success score is 70, with a total of 85% of students achieving it. The results obtained in the first cycle were 64% and 87% in the second cycle. The improvement that occurred shows that podcast media proves to be able to enhance story appreciative listening skills in class VB at SDN Pondok Bambu 02 Jakarta.